Optimizing Communication Overhead while Reducing Path Length in Beaconless Georouting with Guaranteed Delivery for Wireless Sensor Networks - Ruhrup, Stefan; Stojmenovic, Ivan (IEEE transactions on computers, 2013)
Beaconless or contention-based geographic routing algorithms forward packets toward a geographical destination reactively without the knowledge of the neighborhood. Such algorithms allow greedy forwarding, where only the next hop neighbor responds after a timer-based contention using only three messages (RTS, CTS, and DATA) per forwarding step. However, existing contention-based schemes for recovery from greedy failures do not have this property. In this paper, we show that recovery is possible within this 3-message scheme: the Rotational Sweep (RS) algorithm directly identifies the next hop after timer-based contention and constructs a traversal path that ensures progress after a greedy failure. It uses a traversal scheme (called Sweep Circle) that forwards a message along the α-shape of the network and provides recovery paths shorter or equal to the prominent face routing with Gabriel graph planarization. An alternative traversal scheme (called Twisting Triangle) provides even shorter routes on average, as shown by simulations. They both also reduce per-node overall network contention delays. We prove that both traversal schemes guarantee delivery in unit disk graphs. Our traversal schemes avoid planarization and are easy to implement, based merely on the evaluation of a function of a neighbor node's relative position. They can also be used for boundary detection and improve path-length in conventional beacon-based routing.